2019
DOI: 10.1016/j.eurpsy.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Family history of alcohol use disorder is associated with brain structural and functional changes in healthy first-degree relatives

Abstract: Background: Neuroimaging studies of vulnerability to Alcohol Use Disorder (AUD) have identified structural and functional variations which might reflect inheritable features in alcohol-naïve relatives of AUD individuals (FH+) compared to controls having no such family history (FH-). However, prior research did not simultaneously account for childhood maltreatment, any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…We found no significant functional differences between FH 1 and FH 2 subjects in VTA, VS, ACC, or AI during gain anticipation. While this is in line with a number of previous studies (46)(47)(48)(49), it stands in contrast to others reporting functional differences of inconsistent direction between FH 1 and FH 2 subjects during gain anticipation (45,(50)(51)(52).…”
Section: Gain Anticipationsupporting
confidence: 92%
See 1 more Smart Citation
“…We found no significant functional differences between FH 1 and FH 2 subjects in VTA, VS, ACC, or AI during gain anticipation. While this is in line with a number of previous studies (46)(47)(48)(49), it stands in contrast to others reporting functional differences of inconsistent direction between FH 1 and FH 2 subjects during gain anticipation (45,(50)(51)(52).…”
Section: Gain Anticipationsupporting
confidence: 92%
“…For instance, according to the reward deficiency syndrome hypothesis (26), FH 1 subjects, and (abstinent) individuals with alcohol dependence should exhibit similarly decreased neural activation to non-substance-related rewards, resulting in a chronic dysphoric state that can solely be reversed by substance use or other highly rewarding activities (26). While most MIDT studies in FH 1 subjects (46)(47)(48)(49) found no functional differences to healthy subjects during the anticipation phase, other studies showed comparatively increased (45,50,51) or decreased (52) activity in relatives. Differences existed in the VS, ACC, and insula, among others (45,51,52).…”
mentioning
confidence: 99%
“…The frontal lobes being particularly rich in glutamatergic pathways ( Kril et al , 1997 ), they are likely to be especially vulnerable to the severity of AWS. However, we do not exclude that these brain alterations may have been present before alcohol cessation because of the effects of chronic and heavy alcohol consumption or a family history of AUD or comorbidities such as liver disease or thiamine deficiency ( Harper, 2009 ; Chen et al , 2012 ; Filippi et al , 2019 ). In this case, altered brain structure would constitute a vulnerability factor for exhibiting more severe AWS.…”
Section: Discussionmentioning
confidence: 99%
“…These large-scale studies highlight cross-sectional differences whereas prospective studies and comparisons with unaffected family members point towards potential trait related effects. Healthy subjects with a positive family history, show reduced volumes within prefrontal cortices (middle and inferior frontal and orbitofrontal gyrus), mid-cingulate, right insula and bilateral nucleus accumbens (Filippi et al, 2019) and the right parahippocampal gyrus (Sjoerds et al, 2013b). In adolescents with limited alcohol exposure, a positive family history was associated with lower cortical thickness in orbitofrontal and superior parietal cortices in additional to greater impulsivity and impaired memory (Henderson et al, 2018).…”
Section: Structural Changes: Grey Mattermentioning
confidence: 99%